Dietary supplementation with sodium propionate and tributyrin alleviated hepatic lipid deposition and improved the antioxidant capacity and hypoxic stress resistance of spotted seabass (Lateolabrax maculatus) - Cui, Kun; Zhang, Hanle; Yun, Biao; Wang, Jianxue; Qian, Xueqiao; Xue, Min (Frontiers in Marine Science, 2024)
We investigated the effects of dietary supplementation with sodium propionate (SP) and tributyrin (TB) on hepatic lipid deposition and antioxidant capacity of spotted seabass (Lateolabrax maculatus) via an 8-week feeding experiment and a hypoxia stress experiment. The fish were fed five experimental diets: a control diet (CON), a diet supplemented with 2 g/kg SP (SP-0.2%), 4 g/kg SP (SP-0.4%), 2 g/kg TB (TB-0.2%), or 4 g/kg TB (TB-0.4%). No significant difference in growth performance was presented among the groups (P > 0.05). The SP-0.4% and TB-0.2% groups presented significantly lower hepatosomatic and viscerasomatic indexes compared with the CON group. Then, the SP-0.4% and TB-0.2% groups presented stronger resistance to hypoxic stress than the other groups and were analyzed further. The hepatic histology and triglyceride levels revealed that SP-0.4% and TB-0.2% reduced hepatic lipid deposition. Similarly, the downregulation of malondialdehyde and the upregulation of total antioxidant capacity, superoxide dismutase, and catalase activities and the related gene expression levels revealed that SP-0.4% and TB-0.2% improved the antioxidant capacity. Additionally, the RNA sequencing demonstrated that SP-0.4% and TB-0.2% regulated gene expression to a similar extent. Among the 117 differentially expressed genes, 67 genes were enriched in the same pattern, and involved the FoxO signaling, PI3K-Akt signaling, and insulin-related pathways. In conclusion, supplementing SP-0.4% and TB-0.2% as feed additives effectively improved hepatic lipid metabolism, antioxidant capacity, and hypoxic stress resistance of spotted seabass.